PENGARUH ORIENTASI PEMASARAN SYARI’AH DAN INOVASI PRODUK TERHADAP STRATEGI PEMASARAN PADA KSP KOPWAN AISYIYAH SYARI’AH KARANGANYAR - Dewi Pujiani; Juni Trisnowati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
The problem in this study is the many financial institutions that still use the flower or RIBA system. The purpose of this research is to encourage the management of financial institutions to implement sharia systems and avoid the RIBA system. This method of research uses quantitative research methods. Results of calculation of regression coefficient obtained thitung results from the marketing orientation variable of 4.287 and obtained the variable thitung results from the product innovation variable of2,235. Be The number of respondents in this study as much as 60. Based on result data manner SPSS data version 22.0 Fhitung price as big as 29,718. Because the value of Fcount 29.718 > Ftabel 2.77, it can be concluded that the hypothesis is acceptable. Therefore the marketing orientation (X1) and product innovation (X2) simultaneously affect the marketing strategy (Y).